Factors Influencing Post-Study Employment by International Graduates of Regional Universities (Case of Northwestern Federal District of the Russian Federation) - M. Yu. Makhotaeva; O. A. Bakumenko (Высшее образование в России)
The article explores the factors of career mobility choice by international graduates of regional universities, which directly affect their employment in the regions. As a result of the analysis of foreign experience, the authors come to a conclusion that locally-trained international graduates’ employment is an effective tool for replacing the migration outflow from the periphery to megalopolises. A strong positive correlation is proved between the share of international graduates in the normalized student body and the rate of migration growth for the period 2015–2020 in the peripheral subjects in the Northwestern federal district of the Russian Federation. Eight variants of educational migrants’ migration trajectories are identified and described as a combination of two choices: educational and career mobility. Based on the generalization of Russian and foreign approaches, factors of international graduates’ career mobility choice at national, regional, sectoral, university, and individual levels are systematized. Within the online survey of international graduates of Russian regional universities, influence of factors of each level on the choice of a migration trajectory was determined, the influence of the experience of living in the region and studying at the university on changing the migration trajectory was shown. It has been proved that international graduates from the CIS and Baltic countries can make the greatest contribution to the regional economy of the Russian peripheral regions. Recommendations for executive authorities and universities have been developed to stimulate international graduates’ post-study employment in the region of study. As a direction for further research, it seems expedient to develop a model for determining the needs of regional economy in locally-trained international graduates, as well as to test such a model in the peripheral territorial subjects of the Russian Federation.